Design of Mobile Robot Wall Follower Using Microcontroller Using Fuzzy Logic Algorithms - Jejen Samsul Aripin (Jurnal Teknik Informatika C.I.T Medicom, 2019)
Designing and implementing artificial intelligence for car robots is not easy, but with the development of technology, many methods can be used to support the creation of artificial intelligence. The type of control is also very diverse, depending on the object to be created. One of the technologies that can be used to combine these capabilities is fuzzy logic. Where the use of fuzzy logic technology has now developed rapidly and widely in various applications, ranging from information analysis to industrial processes, electronic equipment and others. In this research, logic control design is implemented on the wall follower robot car. Full logic to make movement decision making that combines multiple input data with capabilities, with the decision making technique, the robot wall follower can have the ability to move along the wall stable. This study aims to produce a fuzzy logic design that can be implemented on a wall follower robot car so that when the robot car moves, it can navigate the wall stably. The final result of this research is a logic control design that can be implemented on a wall follower robot car made using wall follower algorithm and Sugeno fuzzy logic to make decisions on the control of the robot car wheel so that when the robot car moves down the wall, the robot car can adjust the distance to the wall to keep it constant.